2021
DOI: 10.1002/er.6973
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of steam methane reforming over a novel multi‐concentric rings Ni/ Al 2 O 3 catalyst pattern

Abstract: Summary Herein, a 2D numerical analysis is conducted to study the steam methane reforming reaction (SMR), which is the dominant method for hydrogen production, over a packed bed reactor embedded with a Ni/Al2O3 catalyst. Aiming to achieve higher methane conversion and low catalyst weight, a comparative study on an SMR reactor consisting of a 1‐m long, 0.04‐m diameter cylinder, is examined under three distinct operative configurations to explore new routes for process intensification. In the first configuration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 69 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…Even though a patterned-bed reactor intuitively contains less catalyst compared to a conventional packed bed of the same size, simulation results suggest that even halving the mass of catalyst reduced the methane conversion rate by only 15%, suggesting the possibility of obtaining high conversion even with a lower catalyst load. Radial patterning of the catalyst, as opposed to axial layering, appears to be a more promising solution, as numerical investigation indicates a capability of achieving an increase in methane conversion while lowering the required catalyst mass (10.6% increase in conversion with a 26.16% decrease in catalyst load) [264]. Crucial aspects of optimization of the process consist in determining the number of layers, their size and the catalyst-to-gap ratio [265].…”
Section: Catalyst Patterningmentioning
confidence: 99%
“…Even though a patterned-bed reactor intuitively contains less catalyst compared to a conventional packed bed of the same size, simulation results suggest that even halving the mass of catalyst reduced the methane conversion rate by only 15%, suggesting the possibility of obtaining high conversion even with a lower catalyst load. Radial patterning of the catalyst, as opposed to axial layering, appears to be a more promising solution, as numerical investigation indicates a capability of achieving an increase in methane conversion while lowering the required catalyst mass (10.6% increase in conversion with a 26.16% decrease in catalyst load) [264]. Crucial aspects of optimization of the process consist in determining the number of layers, their size and the catalyst-to-gap ratio [265].…”
Section: Catalyst Patterningmentioning
confidence: 99%
“…Structured catalysts formed from metal alloys have a level high thermal conductivity [ 5 ]. Moreover, it has been shown that using structured forms of catalysts can improve the efficiency of hydrocarbon catalytic reforming and decrease the overall cost of the process [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%